2012
DOI: 10.1002/art.33485
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil gelatinase–associated lipocalin is instrumental in the pathogenesis of antibody‐mediated nephritis in mice

Abstract: Objective The mechanism by which anti-DNA antibodies mediate lupus nephritis has yet to be conclusively determined. Previously, we found that treatment of mesangial cells with anti-DNA antibodies induced high expression of Neutrophil Gelatinase Associated Lipocalin (NGAL), an iron-binding protein upregulated in response to kidney injury. However, whether NGAL is instrumental in pathogenesis, induced as part of repair, or irrelevant to damage/repair pathways, is not known. Methods To investigate the role of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 34 publications
4
48
1
1
Order By: Relevance
“…Thorsten Berger and Tak M. Mak, The Campbell Family Institute for Breast Cancer Research and the Ontario Cancer Institute, University Health Network (Toronto, CA), and bred at the Einstein Institute for Animal Studies. Generation of NGAL−/− mice on the B6 background has been described; these mice appear normal and display no gross phenotype, as previously reported [8,17,26]. We confirmed that the D1Mit105 lupus susceptibility locus on chromosome 1 in the B6.NGAL−/− strain was of B6 (non-risk), not 129/Sv origin (data not shown).…”
Section: Methodssupporting
confidence: 90%
See 2 more Smart Citations
“…Thorsten Berger and Tak M. Mak, The Campbell Family Institute for Breast Cancer Research and the Ontario Cancer Institute, University Health Network (Toronto, CA), and bred at the Einstein Institute for Animal Studies. Generation of NGAL−/− mice on the B6 background has been described; these mice appear normal and display no gross phenotype, as previously reported [8,17,26]. We confirmed that the D1Mit105 lupus susceptibility locus on chromosome 1 in the B6.NGAL−/− strain was of B6 (non-risk), not 129/Sv origin (data not shown).…”
Section: Methodssupporting
confidence: 90%
“…For cDNA synthesis, reverse transcription was performed from 2 μg of total RNA using the SuperScript II system from Invitrogen. Real time PCR was performed in duplicate or triplicate using the SYBR green PCR mastermix (Power SyBr, Applied Biosystems, Warrington, UK) and the ABI PRISM 7900HT Sequence Detection System (Applied Biosystems), using the ΔCt method as described previously [17]. GAPDH was used as a housekeeping gene for normalization of the CT values for the gene of interest.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CellTiter 96 Solution (Promega) was used for the detection of cell viability. 62 In some of the permeability and viability experiments, the caspase inhibitor z-VAD-fmk (G-Biosciences) was added to the media at a concentration of 20 mM during Fc-TWEAK stimulation.…”
Section: Cell Culturementioning
confidence: 99%
“…Likewise, the expression of Slc40a2, also known as the iron exporter Ferroportin-1, was downregulated in the cortical tubulointerstitium at all time points. In contrast, the gene Lcn2, encoding the protein NGAL, which possesses iron-binding properties and plays a key role in iron metabolism, was significantly upregulated in NTN mice in cortical tubulointerstitial at all time points peaking on day 21 (31.9-fold change, p < 0.0001) [11]. The gene expression of Transferrin was significantly downregulated in whole kidney samples but unchanged in the cortical tubulointerstitium (Table 4).…”
Section: Regulation Of Genes Involved In Iron Metabolismmentioning
confidence: 95%